Not All Competitions Come to Harm! Competitive Biofeedback to Increase Respiratory Sinus Arrhythmia in Managers - Patron, Elisabetta; Munafò, Marianna; Messerotti Benvenuti, Simone; Stegagno, Luciano; Palomba, Daniela (Frontiers in Neuroscience, 2020)
Despite the positive impact on achievement, competition has been associated with elevated psychophysiological activation potentially leading to a greater risk of cardiovascular diseases. Competitive biofeedback (BF) can be used to highlight the effects of competition on the same physiological responses that are going to be controlled through BF. However, it is still unknown whether competition could enhance the effects of respiratory sinus arrhythmia (RSA)-BF training in improving cardiac vagal control. The present study explored whether competitive RSA-BF could be more effective than non-competitive RSA-BF in increasing RSA in executive managers, who are at higher cardiovascular risk being commonly exposed to highly competitive conditions. Thirty managers leading outstanding private or public companies were randomly assigned to either a Competition (n = 14) or a Control (n = 16) RSA-BF training lasting five weekly sessions. Managers in the Competition group underwent the RSA-BF in couples and each participant was requested to produce a better performance (i.e., higher RSA) than the paired challenger. After the training, results showed that managers in the Competition group succeeded in increasing cardiac vagal control, as supported by the specific increase in RSA (p < .001) and root mean square of the successive differences (p < .001). Intriguingly, managers who compete showed the same reduction in resting heart rate (HR; p = .003, ƞ2p = .28), systolic blood pressure (SBP; p = .013, ƞ2p = .20), respiration rate (p < .001; ƞ2p = .46) and skin conductance level (SCL; p = .001, ƞ2p = .32) as non-competitive participants. Also, the same reduction in social anxiety (p = .005; ƞ2p = .25), state (p = .038, ƞ2p = .14) and trait anxiety (p = .001, ƞ2p = .31), and depressive symptoms (p = .023, ƞ2p = .17) emerged in the two groups. Managers competing for increasing RSA showed a greater improvement in their parasympathetic modulation than non-competing managers. Most importantly, competition did not lead to the classic pattern of increased psychophysiological activation under competitive RSA-BF. Therefore, competition could facilitate the use of self-regulation strategies, especially in highly competitive individuals, to promote adaptive responses to psychological stress.